INDUCED SPAWNING AND LARVAL REARING OF THE GREY MULLET LIZA MACROLEPIS (SMITH) - James, P S B R; Rengaswamy, V; Raju, A; Mohanraj, G; Gandhi, V (Indian Journal of Fisheries, 2011)
The paper deals with the results of experiments on induced spawning andlarval rearing of Liza mecrolepis (Smith) during the years 1981 and 1982 atMandapam. Major carp pituitary glands and chorionic gonadotropin were usedfor hypophysation. The effective dosages varied between 600 and 1200 mg and110000 and 340000 I.U. per kg body weight of the fish in the case of major carppituitary gland and chorionic gonadotropin, respectively.' In the combination ofboth, the dose required was 1200 mg and 12000 to 15000 I.U. The size of fullymature egg ranged from 0.70 to 0.74 mm and that of fertilized egg from 0.74 to0.78 mm. The newly hatched larva measured 1.43 mm. Mouth formation wasobserved at 42 h after hatching when the larvae were 2.36 mm. High mortalityoccurred on the third day. The larvae could be reared for seven days, when theyattained a size of 2.47 mm. The larval development is described in detail.